2019
DOI: 10.1039/c9ra05655f
|View full text |Cite
|
Sign up to set email alerts
|

Guanine deaminase provides evidence of the increased caffeine content during the piling process of pu'erh tea

Abstract: Wet piling is a key process for producing pu'erh tea because various components change under the action of microorganisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…3.1.1.20 ) secreted by microorganisms is responsible for hydrolyzing gallates into GA in dark teas during microbial fermentation. ,, This could explain the abundant GA in CDTs. In another study, caffeine levels was found to increase significantly after the microbial fermentation of PU tea, and guanine deaminase was reported to have an important relation to the mechanism underlying the increased caffeine content . In addition, microbial fermentation also has a significant influence on the amino acid profiles of CDTs .…”
Section: Discussionmentioning
confidence: 95%
“…3.1.1.20 ) secreted by microorganisms is responsible for hydrolyzing gallates into GA in dark teas during microbial fermentation. ,, This could explain the abundant GA in CDTs. In another study, caffeine levels was found to increase significantly after the microbial fermentation of PU tea, and guanine deaminase was reported to have an important relation to the mechanism underlying the increased caffeine content . In addition, microbial fermentation also has a significant influence on the amino acid profiles of CDTs .…”
Section: Discussionmentioning
confidence: 95%
“…For determination of xanthine alkaloids, about 0.1 g (fresh weight) powder was extracted with 1.5 ml 80% (v) methanol in water and sonicated for 30 min at 12°C. All samples were mixed up and down every 10 min and centrifuged at 10,000 rpm for 10 min, then the supernatants were filtered through 0.22 µm membranes before UPLC analysis ( Pan et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Xanthine alkaloids in the extracts were measured using an ACQUITY UPLC H-Class instrument (Waters, the United States) and separated on a ACQUITY UPLC BEH C18 Column (2.1 × 100 mm, 1.7 μm in particle size and 130 Å in pore size) at a flow rate of 0.3 ml/min at 35°C with 1 μl sample volume, the mobile phase was selected as 0.2% (v) acetic acid in water (A), and methanol (B), and the gradient elution was as follows: B 6% from 0 to 2 min, to 8% at 3.5 min, to 10% at 4.5 min, to 18% at 7.5 min, to 26% at 10.5 min, to 80% at 13.5 min and kept at 80% for 1 min, to 6% at 16 min and kept at 6% for 1 min, the detection wavelength was set to 278 nm ( Li et al, 2017 ; Pan et al, 2019 ). Xanthine alkaloids were identified by using a high resolution quadrupole time-of-flight mass spectrometry (QTOF MS) on the positive-ion mode, the Agilent 1290 UPLC was interfaced with an Agilent 6545 Q-TOF LC/MS system equipped with electrospray ionization source (ESI).…”
Section: Methodsmentioning
confidence: 99%
“…It belongs to the family of methylxanthine alkaloid and is a psychoactive stimulant drug which can be usually extracted from plants like coffee, guarana, cacao, yerba mate etc. ( Pan et al, 2019 ). CAF can be used for the pharmaceutical drug preparations as an analgesic adjuvant, treat conditions like physical fatigue, drowsiness ( Mou et al, 2019 ), apnea of prematurity ( Philip et al, 2018 ) and bronchopulmonary dysplasia in premature infants ( Principi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%